The Development of Animated Powtoon Media in Teaching Personal and Official Letters for Grade 7 at SMPN 1 Sitiung - Amar Salahuddin; Aprimadedi Aprimadedi; Deviana Putri (The Future of Education Journal, 2025)
This study aims to develop Powtoon-based learning media on material to recognize personal letters and official letters for class VII students in Sitiung 1 Public Middle School. This study uses the Research and Development (R & D) method with a 4D development model, which includes the define stage, design, develop, and disseminate. This research was conducted at the Sitiung 1 Public Middle School in the 2024/2025 school year with the research subjects was a class VII student amounting to 31 people. Data collection techniques are carried out through questionnaire response students and teachers, as well as validation sheets involving media experts, material experts, and luition experts. The results of this study showed researchers to produce Powtoon-based learning media as material learning media comparing personal letters and official letters, the media said valid, seen from the validation of media experts obtained a score of 81.25% and included the "Very Valid" category, the validation of the material expert obtained a score 90.63% included the "Very Valid" category, the validation of linguists obtained a score of 92.86% including the "Very Valid" category. This means that learning media are worthy of use by educators and students. The results of the assessment of practicality carried out by educators obtained a score of 88.64% including the category of "very valid" and class VII students obtained a score of 84.99% including the "Very Valid" category. It can be concluded that podcast-based learning media that have been developed by researchers are feasible to use, because they have fulfilled the category, valid, practical, and effective.